The politics of technology and site location: impact of state interventionism on an Indian public sector firm - Dilip Subramanian (Netcom)
Can an industrial organisation simultaneously fulfil economic and social functions, that is to say successfully reconcile its own priorities of optimal resource utilisation and productive efficiency with the larger objectives of social justice defined for it by public authorities? This is the central question this paper whose compass is restricted to the 1980s asks, and seeks to answer on the basis of a study of locational and technology choices at a big public sector manufacturing firm, Indian Telephone Industries. It will show how decisions pertaining both to the implantation of new state-owned factories and the sourcing of technology were shaped not by an economic rationale but a political one where employment generation took precedence over all other considerations. This was a consequence, on the one hand, of the paradigm of state-initiated industrial development embraced by India after Independence in 1947 and which held out the promise of future prosperity for the population at large; on the other, of the mode of governance prevailing in public enterprises where state interventionism rhymed with the complete loss of autonomy for managements. The paper concludes by pointing out that however justified the redistributive goals allocated to public enterprises from the standpoint of improving living standards, they proved highly detrimental to their efficient working as well as onerous for the exchequer.